Health promoting properties of blueberries: a review - Silva, Sara (2018)
With the strengthening of the link between diet and health, several foodstuffs have emerged as possessing potential health benefits such as phenolic rich fruits and vegetables. Blueberries, along with other berries, given their flavonoid and antioxidant content have long since been considered as a particularly interesting health promoting fruit. Therefore, the present work aimed to compile the existing evidences regarding the various potential benefits of blueberry and blueberry based products consumption, giving particular relevance to in vivo works and epidemiological studies whenever available. Overall, the results demonstrate that, while the evidences that support a beneficial role of blueberry and blueberry extracts consumption, further human based studies are still needed.